Surface Energy Changes Involved in Apatite Formation in Copper-Containing Bioactive Glasses - Duarte,Camila Miranda Fonseca (2022)
Abstract The aim of this work was to use the Washburn capillary rise method to evaluate changes in surface energy promoted by the insertion of CuO in a 58S glass and its implication in bioactivity. The presence of CuO decreased the surface wettability by decreasing the Lewis acid-base component γSAB and increasing the Lifshitz-van der Waals component γSLW. The insertion of CuO also diminished the value of the electron donor parameter γS-; i.e., the number of negative groups. This was accompanied by a nonuniform apatite formation on the surface, likely because the presence of CuO-rich regions with lower electron donor values impaired the adsorption of Ca2+, preventing uniform apatite precipitation. Therefore, surface energy was extremely sensitive to small physical and chemical changes in the glass structure and the behavior of the electron donor parameter could be used as an adequate probe to predict glass bioactivity.